Who Was Honored by “Truthful Khan”, “Coveted Khan” and Their Descendants - Gennady N. Garustovich (Золотоордынское обозрение)
The objective of this study is to consider issues of the features of the pagan beliefs – the primordial religion of shamanism of the Turks and Mongols – described in writings of the authors of the Middle Ages: Chinese, Arab, Western, Russian, etc. (which act as the main research materials). Novelty of the research: until now the specific realities of the Turko-Mongol shamanism in Russia have been studied, but still not fully, despite the publication of numerous works of historians, anthropologists, archaeologists, linguists and specialists in other scientific and educational disciplines. As a result of the work, it appears that the authors of medieval narratives managed to notice series of interesting and important elements of the traditional religion of the steppe people. The deification by nomads of natural disasters contributed to the formation of their polytheism, with a large list of spirits and demons, and the development of complex branched rituals; it led to the isolation of their stratum of professional clergy – of the shamans (kams, buge, udogan). Priestly class served as intermediaries between the community of living people and the supernatural world of gods and genii, communicating with the ideal world through its spirit helpers (in the rites). Ministers of religion in society performed number of important functions (protective-preservative, healing, cleansing, conservative-traditionalist, et al.). As the narrative sources chroniclers paid little attention to the structure of the pantheon of gods and dogmas of shamanism, this paper objects rather the shamans’ function in ritual practice. The priests involved in family rituals (at the funeral and wake, with courtship and the birth of a child) were carriers of traditions, healed sick and treated animals, “struggled” with evil spirits, magically influenced their enemies, guessed and predicted future, and most importantly – they were managers of regular generic and tribal ancestors sacrifices. Shamans belonged to the khans’ approximates providing their ideological support and resolving legitimation problems of the boards of the Turks and the Mongols in early class period. Their life experience and knowledge of the elements of nature (characteristics of the environment) did not rule out the use of animism and magical practices (cleansing power of fire, stone “jada”, etc.).